Efecto de Alquernat Nebsui sobre los parámetros productivos y calidad de canal, en comparación al clorhidrato de ractopamina, en el último mes de engorde de cerdos comerciales, en la irrigación Majes, Arequipa –2020 - Arratea Cama, José Omar (2022)
Caylloma province, Arequipa region. This irrigation is located 100 km from the city of Arequipa at 1400 meters above sea level, between 16°39'20" south latitude and 16°39'12" west latitude. The experiment and data processing were carried out between July and October 2020, in order to evaluate the effect of the additive "alquernat nebsui" on production parameters and carcass quality, compared to "ractopamine hydrochloride", in the last month of fattening of commercial pigs. The following variables were considered: live weight variation and gain, feed conversion, morbidity, carcass yield, backfat thickness and economic merit. A completely randomized design with fourteen replicates was used for the statistical evaluation of the results. Three treatments were evaluated: a standard ration as a control diet (T1), a second treatment with the same standard ration but with the inclusion of ractopamine with 10 ppm of active ingredient (T2) and a third treatment with the same standard ration but with the inclusion of 0.05% alquernat nebsui (T3). The treatments were evaluated in 42 meat pigs in the fattening stage in two commercial farms with an average weight of 48.19 ± 8.5 kg during the last 28 days of fattening, repeating the same experiment in each farm, in order to minimize the experimental error due to genetic and environmental variations. Feed consumption was the same in all animals, since the farms were fed on a restricted basis, with an average of 2.125 kg/day/pig. With the use of alquernat nebsui, better pig weights were achieved in the last 15 days of fattening, compared to the rations with ractopamine hydrochloride and the control ration. Average daily gains per pig were 0.772, 0.813 and 0.868 kg for treatments T1, T2 and T3, respectively. These values implied a 5.3% higher gain with ractopamine hydrochloride and a 12.5% higher gain with the use of alquernat nebsui. However, the differences found were not statistically significant. Daily vii feed conversions were 2.86, 2.73 and 2.60 for treatments T1, T2 and T3, respectively. These values implied 4.8% lower feed conversion with ractopamine hydrochloride and 9.1% lower feed conversion with the use of alquernat nebsui. However, the differences observed were not statistically significant. The measurement of the degree of diarrhea, indicative of morbidity in the experimental pigs, was 1.26, 1.23 and 1.09 on average for treatments T1, T2 and T3, respectively. These values indicated that the feces of the pigs evaluated were almost always normal and well formed. However, there was a tendency towards greater health in the pigs that received the ration with alquernat nebsui. Carcass yields were 73.5, 73.3 and 73.9% for treatments T1, T2 and T3, respectively. The use of ractopamine hydrochloride and alquernat nebsui did not influence this variable. Backfat thickness was 1.82, 1.45 and 1.51 cm for treatments T1, T2 and T3, respectively. These values implied 20% less backfat thickness with the use of ractopamine and 17% less with the use of alquernat nebsui compared to the control ration. Upon statistical analysis, backfat thickness with the use of these additives was significantly lower than that measured with the control ration. Feeding costs per kilo of live weight gain, as an indicator of economic merit, were on average: 3.46, 3.51 and 3.10 soles for treatments T1, T2 and T3, respectively. A 10.4% lower cost was observed with the use of alquernat nebsui compared to the control ration and 11.5% compared to ractopamine hydrochloride. However, these differences were not statistically significant.